2020
DOI: 10.17712/nsj.2020.1.20190058
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of antidepressant-induced sexual dysfunction among psychiatric outpatients attending a tertiary care hospital

Abstract: ‫العيادات‬ ‫مرضى‬ ‫في‬ ‫اجلنسي‬ ‫الوظيفي‬ ‫اخللل‬ ‫انتشار‬ ‫لقياس‬ ‫األهداف:‬ ‫الباروكستني‬ ‫أو‬ ‫بالفلوكستني‬ ‫عوجلوا‬ ‫الذين‬ ‫النفسية‬ ‫لألمراض‬ ‫اخلارجية‬ ‫امليرتازابني.‬ ‫أو‬ ‫الفينالفاكسني‬ ‫أو‬ ‫جامعة‬ ‫مستشفى‬ ‫في‬ ‫رجعي‬ ‫بأثر‬ ‫مقطعية‬ ‫دراسة‬ ‫أجريت‬ ‫املنهجية:‬ ‫سن‬ ‫فوق‬ ‫املرضى‬ ‫جميع‬ ‫دعينا‬ ‫عمان.‬ ، ‫مسقط‬ ‫قابوس،‬ ‫السلطان‬ ‫النفسية‬ ‫العيادة‬ ‫حضروا‬ ‫الذين‬ ‫الدراسة،‬ ‫في‬ ‫للمشاركة‬ ‫عام‬ 18 ‫أو‬ ‫فينالفاكسني‬ ، ‫باروكستني‬ ‫فلوكستني،‬ ‫من‬ ‫كال‬ ‫واستخدموا‬ ‫لتوثيق‬ ‫البيانات‬ ‫جلمع‬ ‫ور… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 22 publications
0
8
0
1
Order By: Relevance
“…The activation of the postsynaptic serotonin (5-HT) 2A receptor is suggested to be a significant contributor to antidepressant-related sexual dysfunction (4). Paroxetine showed a higher risk for sexual dysfunction compared with other SSRIs (5,8,9).…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…The activation of the postsynaptic serotonin (5-HT) 2A receptor is suggested to be a significant contributor to antidepressant-related sexual dysfunction (4). Paroxetine showed a higher risk for sexual dysfunction compared with other SSRIs (5,8,9).…”
Section: Introductionmentioning
confidence: 93%
“…Many people experience a kind of sexual dysfunction related to antidepressants (5). SSRI-induced sexual dysfunction may be up to 80% (2).…”
Section: Introductionmentioning
confidence: 99%
“…To the Editor I have read with interest the original article entitled "Prevalence of antidepressant-induced sexual dysfunction among psychiatric outpatients attending a tertiary care hospital" by Mohammed AlBreiki et al, published in Neurosciences journal. 1 I want to commend the authors for selecting an interesting topic with a wide range of age, absence of organic diseases that causes sexual dysfunction, and the patients used 4 different antidepressant compounds. There are certain methodological concerns which might create a response bias among patients suffering from sexual dysfunction.…”
Section: Prevalence Of Antidepressant-induced Sexual Dysfunction Among Psychiatric Outpatients Attending a Tertiary Care Hospitalmentioning
confidence: 99%
“…According to previous studies, SDs are reported by 25% up to 75% of patients taking SSRIs and by 30% up to 93% of those taking TCAs [ 1 , 3 ]. SDs may engage the phase of the sex drive (loss of libido), the arousal (lubrication in women, erectile function in men), the ejaculation, and orgasm [ 4 ]. Data collected in recent decades confirm that there are significant differences in antidepressant-induced SD (AISD) between men and women.…”
Section: Introductionmentioning
confidence: 99%